Early Stage Diagnosis of Oral Cancer Using 1H NMR–Based Metabolomics - Tiziani, Stefano; Lopes, Victor; Günther, Ulrich L. (Neoplasia (New York, N.Y.), 2009)
Oral cancer is the eighth most common cancer worldwide and represents a significant disease burden. If detected at an early stage, survival from oral cancer is better than 90% at 5 years, whereas late stage disease survival is only 30%. Therefore, there is an obvious clinical utility for novel metabolic markers that help to diagnose oral cancer at an early stage and to monitor treatment response. In the current study, blood samples of oral cancer patients were analyzed using nuclear magnetic resonance spectroscopy to derive a metabolic signature for oral cancer. Using multivariate chemometric analysis, we obtained an excellent discrimination between serum samples from cancer patients and from a control group and could also discriminate between different stages of disease. The metabolic profile obtained for oral cancer is significant, even for early stage disease and relatively small tumors. This suggests a systemic metabolic response to cancer, which bears great potential for early diagnosis.